ESTUDO QUÍMICO E BIOATIVIDADES DE Baccharis uncinella DC. - Ascari, Jociani (2007)
Baccharis uncinella (Asteraceae), popularly known as vassoura, is little known from the chemical point of view, with only two earlier scientific works on their secondary metabolites - the volatile constituents. In the present study, the essential oil from the leaves of B. uncinella and nine extracts obtained in a Soxhlet apparatus with organic solvents starting from the leaves, barks and log were analyzed by CCD, UV and IV and submitted to activity tests against microorganisms; besides, the interactions between the aqueous extract of the leaves with human erytrocytary cells of the sanguine types O+, O-, A+ and B+ were also analyzed. In the antimicrobial tests, the microfungus Candida albicans, as well as the Gram-positive Bacillus cereus, Enterococcus faecalis, Staphylococcus aureus and S. saprophyticus and the Gram-negative bacteria Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa were used. The essential oil showed action against B. cereus, S. aureus and C. albicans, in the same way as all of the organic extracts, but the growth of S. saprophyticus was not inhibited by no one of the extracts. The extracts of the barks, when compared with those obtained from other parts of the plant, were active against the largest number of microorganisms and presented the more strong activities. The minimum inhibitory concentration of the essential oil was estimated as 100/mL against S. aureus as well as against C. albicans, wich could be considered a moderate antimicrobial activity. We have isolated small amounts of the three major phenolic components found in the leaves, and the analysis of their UV- and IR-spectra showed the structural features of hydroxylaryl-propenoic acids for these compounds that were found for the first time in this plant species. The analyses of GC-MS of the essential oil produced by hydrodistillation of the leaves collected at the Paraná State presented low monoterpene content (2.29%) and the following sesquiterpenes as the main components: spathulenol 17.20%, caryophyllene oxide 16.20%, transcaryophyllene 10.48%, eudesmol 7.55%, germacrene D 6.28% and cadinol 5.18%. Another oil sample was obtained using the same conditions, but starting with leaves collected in the highland area of Santa Catarina, also presented spathulenol as the main component (15.83%), but it contained 36% in monoterpenes, a very similar composition to those published for samples from the State of Rio Grande do Sul. The interactions among the aqueous extract of the leaves with human erytrocytes isolated from the sanguine types O+, O-, A+ and B+, being verified that the extract presents a non-lytic activity in the analyzed concentrations of 22, 110 and 220/mL. This non-hemolytic profile was observed as similar for all tested blood types. The serological types A+ and O- presented a similar pattern of free Hb oxidation in solution, and the same profile was observed in the new suspension of the precipitate. In the analysis of MEV we observed the qualitative aspects regarding the interaction of the aqueous extract with the architecture of the erythrocyte. In the assays of DPPH with low concentrations, 1.5 x 10-4 and 7.8 x 10-5 mg/mL, it was possible to quantify a partial reduction in the free radicals concentration of 20.10% and 9.25% respectively.